TYPIFICATION OF WATER-LAND CONTACT ZONES WITHIN THE DNIEPER-BUG ESTUARY REGION - Коржов, Євген (SWorldJournal, 2025)
The article presents a typology of the contact zones "water-land" of the Dnieper-Bug estuary region. According to the data of field studies within the studied area, we have identified three main types, which include eight subtypes of contact zones at the